Study on the interaction mechanism between the contra-rotational shear deep soil mixing drilling tool and the soil - Xue, Zizhou; Liu, Zhong; Fang, Shizheng; Xiong, Liwei; Wu, Kun (Frontiers in Built Environment, 2025)
Deep soil mixing piles are established for soft soil stabilization, yet the internal mechanism by which drilling tools achieve complete soil-cement homogenization remains unclear, hindering precise quality control in column formation. In this paper, a new type of contra-rotational shear deep soil mixing (CS-DSM) drilling tool was proposed and the detailed design information was thoroughly introduced. The discrete element modeling method was applied to establish a coupling model of CS-DSM drilling tool and soil verified by a laboratory model experiment. Soil particle moving path analysis quantified mixing dynamics during drilling-down and drilling-up phases. The results explained the internal mechanism that the soil particles could be fully sheared, stirred, and mixed in the horizontal and vertical directions to form a uniform soil cement column. The average VC of particle X1-X3 was 1.9 times larger than that of particles Y1-Y3, which indicated that soil particles along the x-axis and y-axis exhibited distinct moving patterns. The mixing efficiency during drilling-down and drilling-up was quite different, and the VC during the drilling-down process could be 146.7 times larger than that during the drilling-up process. In practice, reducing drilling speed or increasing rotational velocity during drilling-down enhances CS-DSM pile quality under identical conditions.